Implementasi Manajemen Pendidikan Karakter dalam Menangani Bullying di Sekolah Dasar - Sri; Purnami, Agustina Sri (Media Manajemen Pendidikan, 2025)
This study aims to analyze the implementation of character education management in preventing bullying at SD Negeri Percobaan 3 Pakem Sleman. The research focuses on planning, organizing, implementing, and supervising character education as a preventive strategy against bullying in elementary school environments. A qualitative descriptive method was employed, utilizing interviews, observations, and document analysis as data collection techniques. The research subjects consisted of the principal, teachers, and school committee members. The findings indicate that character education is integrated into classroom instruction, extracurricular activities, and school culture through a collaborative approach involving all school stakeholders and the broader community. The primary strategy adopted is the Pola Asuh Pendidikan Karakter Keluarga 28 (Family-Based Character Education Model 28 or Pasukan Raga 28), which emphasizes values of collaboration, empathy, and social responsibility. Monitoring and evaluation are conducted multilaterally by the principal, teachers, and the school committee through continuous supervision and assessment of character development outcomes. This study contributes to the development of a structured and participatory model of character education management in the context of primary education.